Analysis of Community Participation in the Musrenbang in Tanjungpinang Timur Village, Bukit Bestari Subdistrict, Tanjungpinang City - Azahra Ashilah; Bismar Arianto; Adhe Fadli Farhan (CV SCRIPTA INTELEKTUAL MANDIRI, 2026)
This study investigates the operational realities of public participation within the municipal development planning forum (Musrenbang) in Tanjungpinang Timur Village, Bukit Bestari Subdistrict, Tanjungpinang City. Utilizing an empirical sociolegal research design, the investigation juxtaposes statutory mandates under Law Number 25 of 2004, Law Number 23 of 2014, and Minister of Home Affairs Regulation Number 86 of 2017 against field execution practices. Data were gathered through in depth interviews with eleven key informants and procedural documentation analysis, subsequently processed using the interactive qualitative model of Miles and Huberman. Findings demonstrate that participatory planning mechanisms function primarily as procedural compliance routines rather than genuine platforms for deliberative democracy. Structural reliance on neighborhood elite delegation restricts direct citizen involvement, while bureaucratic filters during municipal technical reviews systematically prioritize physical infrastructure projects over socio-economic welfare proposals. Consequently, the local planning framework reflects top down administrative dominance, reducing community input to a symbolic legitimization tool. Reforming this system requires institutionalized legal guarantees, binding participatory budgeting mechanisms, and unmediated deliberative spaces to ensure equitable regional development and meaningful grassroots empowerment.